Studi Perkembangan Pariwisata Dan Pengaruhnya Pada Lingkungan Fisik Di Pantai Balangan, Desa Ungasan, Jimbaran - Yulien Prastika; I Nyoman Sunarta (JURNAL DESTINASI PARIWISATA, 2018)
The background of this research is Balangan beach in the town of Jimbaran that has problems such as facilities development in the coastal setback and the trash accumulating in the coastal setback after tourism development in the area. Based on the above research that revealed two problems, namely how was the tourism development in Balangan beach? And how was the effect of tourism development in physical environment in Balangan beach? To express the above problem this research using primary data source, while type of data used is the qualitative data and quantitative data. The method of data collection through observation and interviews. With data analysis using descriptive qualitative method. The results of the research that the tourism development in Balangan beach on the development phase. And the effect of tourism development in physical environment were the accommodation and restaurant increase, the attraction increase with many activity, the path heading towards the beach was repaired, the water stock the source comes from a well in Cengiling village, and the garbage dump effect was bad. Keywords : tourism development, effect, physical environment.